EPIDEMIOLOGICAL CHARACTERISTICS OF THE COVID-19 DISEASE IN THE SOUTH BANAT DISTRICT IN 2021 - Stanišić, Olivera (HEALTH CARE, 2023)
Introduction/Aim: The new coronavirus or SARS- CoV-2, in a short period of time after its appearance in Wuhan, China at the end of 2019, quickly spread throughout the world, which is why on March 11, 2020, the World Health Organization declared a covid pandemic 19. Over 750 million confirmed cases of COVID-19 and 6.9 million deaths have been reported so far. The aim of this research is to analyze the demographic and clinical characteristics of people with COVID-19 in the South Banat District in 2021.Methods: The paper used a descriptive study that included 34,912 subjects of both sexes and all ages. The research included all patients in whom SARS-CoV-2 infection was laboratory-confirmed by a rapid antigen or RT-PCR test in 2021, in the South Banat District, without data on whether the infection occurred for the first time or not. For the purposes of this analysis, data on demographic and clinical characteristics of patients with COVID-19 disease were used. Incidence was used as an indicator of morbidity. As the denominator of the incidence rate, the number of inhabitants was used for the Južno Banat district and eight associated municipalities (Alibunar, Bela Crkva, Vršac, Kovačica, Kovin, Opovo, Pančevo and Plandište), according to the 2011 census. All data were processed in the IBM SPSS Statistics 22 (SPSS Inc., Chicago, IL, USA) software package.Results: In 2021, 34,912 sick patients with confirmed SARS-CoV-2 infection were reported in the South Banat District. The incidence rate of COVID-19 was 11,885.7/100,000 inhabitants. The highest incidence rate was recorded in the municipality of Kovačica (15,618.7/100,000) and in the 40-49 age group (16,040.9/100,000). In all age groups, the incidence rates for COVID-19 were higher for women than for men, except for ages 0-14 and 60 and over. In October 2021, the highest incidence rate of the COVID-19 disease was registered (2759.3/100,000). 8% of patients had a severe clinical picture, and 22.8% had at least one comorbidity, of which hypertension (62.1%) was the most common. The most frequently recorded symptom of the disease was fever (73.6%). Complete vaccination was carried out in 17.9% of patients, and the most frequently administered vaccine was Sinopharm (69.9%).Conclusion: It is necessary to constantly educate the population about the importance of immunization, especially people with a higher risk of developing a more severe form of the covid-19 disease.
Keywords: SARS-CoV-2 infection, COVID-19 disease, disease severity, gender, age, comorbidities, vaccination status